2021
DOI: 10.1055/s-0041-1736625
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Multitasking and Workflow Fragmentation in Electronic Health Records among Emergency Department Clinicians: Using Time-Motion Data to Understand Documentation Burden

Abstract: Background The impact of electronic health records (EHRs) in the emergency department (ED) remains mixed. Dynamic and unpredictable, the ED is highly vulnerable to workflow interruptions. Objectives The aim of the study is to understand multitasking and task fragmentation in the clinical workflow among ED clinicians using clinical information systems (CIS) through time-motion study (TMS) data, and inform their applications to more robust and generalizable measures of CIS-related documentation burden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…While this is common practice, a high level of multitasking adds to the experienced documentation burden. 17 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this is common practice, a high level of multitasking adds to the experienced documentation burden. 17 22 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, streamlining workflow and aligning the documentation process with clinical workflow might also be effective in reducing the documentation burden. 22 26 Lindsay and Lytle found that this can result in an 18.5% reduction in documentation time. 26 Minimizing interruptions of workflow, for example, by being critical of which decision support alerts should and which should not be used, can also contribute to reducing the burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breaks in attention within each of these two units increase clinicians' cognitive workload, which in turn contributes to burnout. 6 7 8 9 10 11 12 The two interactions impede each other, with EHR tasks and direct patient contact typically overlapping.…”
Section: Cognitive Overload—a Situation Where Undivided Attention Is ...mentioning
confidence: 99%
“…6 An ever important consideration when designing decision support tools is the potential burden that such tools can place on clinicians when improperly designed. [7][8][9] User-centered design techniques applied from the design stage can mitigate some of this burden. 10,11…”
Section: Available Knowledge and Knowledge Gapsmentioning
confidence: 99%